KONSEP PERKEMBANGAN MANUSIA DALAM AJARAN ISLAM - Eka Safliana (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2021)
Development is something that can not be neglected by human in living. In addition, the development of prenatal period has an urgent role to continue the humam’s life. This research used descriptive method, it is qualitative because the writer tried to analize it deeply. It is about humamn development consept of Islam. This research is about Quranic verses of human prenatal development, it could be concluded that those Quranic verses which discuss about human prenatal development the are certain QS al-mukminuun, 23: 13-14, tema tertentu. QS al-Qiyamah, 36-37. QS an-Najm: 45-46. QS al-insan: 2. QS. Al-‘Alaq, 96: 1-3. QS as-Sajdah: 7-8.